Regulating Membership: Explaining Restriction and Stratification of Family Migration in Europe. (September 2015) - Block, Laura
In many European countries, family migration polices have grown increasingly restrictive in the past decade. At the same time, family migration rights are often highly stratified—for instance, depending on the nationality and also the occupation of the sponsor or the incoming family members, more or fewer conditions have to be fulfilled for reunification. This article maps out a framework for the analysis of family migration policies focusing on the concept of "membership." Policies requiring certain levels of income, integration, or "attachment" all assess the membership of applicants in various ways. The stronger one's membership and belonging to the community is considered to be, the stronger the claim to family migration rights. Different dimensions of membership, such as legal, socioeconomic and ethnocultural membership can thus be useful lenses of analysis to grasp how and why restrictive and stratifying family migration policies are conceptualized, justified, and implemented across Europe.